1994
DOI: 10.1016/0375-9474(94)90713-7
|View full text |Cite
|
Sign up to set email alerts
|

The delta-hole model at finite temperature

Abstract: The spectral function of pions interacting with a gas of nucleons and ∆ 33 -resonances is investigated using the formalism of Thermo Field Dynamics. After a discussion of the zero ∆-width approximation at finite temperature, we take into account a constant width of the resonance. Apart from a full numerical calculation, we give analytical approximations to the pionic spectral function including such a width. They are found to be different from previous approximations, and require an increase of the effective ∆… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…We found that the short range correlation largely suppresses the ph excitation but enhances the ∆h excitation very much. The pion dispersion relations are quite different from those calculated in the nonrelativistic approximation 2,8 . The short range correlation has a large effect on all branches of the pion dispersion relation.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…We found that the short range correlation largely suppresses the ph excitation but enhances the ∆h excitation very much. The pion dispersion relations are quite different from those calculated in the nonrelativistic approximation 2,8 . The short range correlation has a large effect on all branches of the pion dispersion relation.…”
Section: Discussioncontrasting
confidence: 73%
“…An alternative way to construct the short range correlation to the polarization insertion is as follows 8,12 :…”
Section: Shown Inmentioning
confidence: 99%
See 1 more Smart Citation
“…[50,10,51] such a procedure has been used in order to account for the finite ∆-isobar width in the pion self energy. We see that the value ImA R 0 given by eq.…”
Section: Contribution Of One-loop Diagram With Full Fermion Propagatorsmentioning
confidence: 99%
“…2 − -resonances is given by [53] (also see [54], who treated coupling of pions to resonance hole excitations)…”
Section: A Vector Meson Self Energiesmentioning
confidence: 99%